Modelo de auto cuidado de Dorothea Orem en mujeres pre menopaúsicas que acuden al Centro de Salud Cuatro Esquinas periodo enero – abril del 2019 - García Llumitaxi, Elizabeth Leticia (2020)
The lack of a process that seeks to know if there is adequate self-care in premenopausal women in a community where there are more than 200 patients diagnosed with this syndrome began the completion of the project called: “DOROTHEA OREM SELF CARE MODEL PRE MENOPAUSIC WOMEN GOING TO THE FOUR CORNER HEALTH CENTER PERIOD JANUARY - APRIL 2019 ” with the aim of: determining the relevance of self-care based on the model already stated, so it was essential to stipulate specific objectives to know basic conditioning factors, compliance with requirements and thus be able to propose a material that contributes to self-care. In order to reach the culmination of the research work, several bibliographical sources were investigated and thus to be able to base the project, the development of the theoretical framework is of vital importance since it allows the researchers to soak up the subject and understand both in a particular and general way the object of study; In the development of the methodological framework it has been established that the research is descriptive, whose sources are both documentary and field, with both quantitative and qualitative data with a transversal design since the data is obtained at a specific time without the need for follow-up, the calculation of the sample was carried out by dispersing the population, determining that one works with 146 premenopausal women, of which it has been established that a predominant group is considered indigenous, with no level of education who are dedicated to agriculture where the age at which this syndrome occurs most frequently is 45 years (fashion), while the self-care they maintain does not meet the requirements according to the model under study since they do not feed properly, they do not perform walks, do not have a good rest, consume alcoholic beverages, there is no adequate family communication and tamp Oco regularly attend medical appointments, being the basis by which the guide for proper self-care was designed